Challenges in coordination process for tall building construction - Mohd. Noor, Mohd. Nasir (2010)
The coordination process for tall building construction is a very complex process. It involves many parties and special construction method and technology. However in today’s current practice of tall building construction, many problems have occurred and contributed to the failure of the project. The common problems faced are delays in completion, cost over run and poor standard quality. One of the reasons is due to inefficient or poor coordination process especially during construction. Therefore, this study is carried out to investigate the challenges in coordination process in tall building construction. The methodologies adopted for this study include interview with expert panel and questionnaire survey distributed among those who are experience in tall building construction. The finding from this study revealed that the construction industry particularly in Malaysia need to be improve with regards to the coordination process. Currently, there are there are a lot of problems associated with coordination process of tall building construction especially during construction stage. These problems have been identified in this report. Then this study also makes some proposal for improving current coordination process. Among the proposal identified in this report are close tracking and monitoring for work program, implementation of quality management system such as ISO certificate and also implementation of new industrial building system (IBS).